2012
DOI: 10.3174/ajnr.a3045
|View full text |Cite
|
Sign up to set email alerts
|

Tract-Based Spatial Statistical Analysis of Diffusion Tensor Imaging in Pediatric Patients with Mitochondrial Disease: Widespread Reduction in Fractional Anisotropy of White Matter Tracts

Abstract: BACKGROUND AND PURPOSE:Often diagnosed at birth or in early childhood, mitochondrial disease presents with a variety of clinical symptoms, particularly in organs and tissues that require high energetic demand such as brain, heart, liver, and skeletal muscles. In a group of pediatric patients identified as having complex I or I/III deficits on muscle biopsy but with white matter tissue appearing qualitatively normal for age, we hypothesized that quantitative DTI analyses might unmask disturbance in microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The observed reduced FA in the cerebral cortex, external capsule and cerebral peduncle in Ndufs4 −/− brain, is in line with white matter diffusivity changes previously described in patients with mitochondrial disorders. Widespread reductions in FA (including the external capsule and cerebral peduncles) were found in three different clinical studies; in a group of pediatric patients, identified as having complex I or complex I/III deficits, among patients with m.3243A > G mutation and patients with OPA1 autosomal dominant optic atrophy and Leber’s hereditary optic neuropathy 61 63 . Not only FA was affected in the cerebral cortex and external capsule, we also found a significant increase in lipid peroxidation in these brain areas.…”
Section: Discussionmentioning
confidence: 97%
“…The observed reduced FA in the cerebral cortex, external capsule and cerebral peduncle in Ndufs4 −/− brain, is in line with white matter diffusivity changes previously described in patients with mitochondrial disorders. Widespread reductions in FA (including the external capsule and cerebral peduncles) were found in three different clinical studies; in a group of pediatric patients, identified as having complex I or complex I/III deficits, among patients with m.3243A > G mutation and patients with OPA1 autosomal dominant optic atrophy and Leber’s hereditary optic neuropathy 61 63 . Not only FA was affected in the cerebral cortex and external capsule, we also found a significant increase in lipid peroxidation in these brain areas.…”
Section: Discussionmentioning
confidence: 97%
“…For example, demyelination is associated with an increase in the radial (short-axis) term, whereas axonal damage is associated with a decrease along the axial (longaxis) direction (10,11). In our prior work, extensive changes in FA were observed in a mitochondrial disease sample, including widespread reduction of FA in the white matter tracts, with an increase in the radial term and no change in the axial term (13). While acquisition parameters can impact the specificity of radial or axial terms (14), the general pattern of change has the potential to be informative about underlying mechanisms.…”
mentioning
confidence: 81%
“…FA has been used extensively in the research setting to characterize central nervous system tumors, tumor infiltration, and peritumoral edema (18)(19)(20). Decreased FA is common in white matter injury, typically attributed to its association with an increased radial diffusivity (λr); this is observed in periventricular white matter in hydrocephalus, posterior reversible encephalopathy syndrome, peritumoral edema (10), and mitochondrial disease (13). A few disease states are reported in which a decreased FA is associated with decreased axial diffusivity (λa), including radiation injury (21).…”
Section: Pediatric Diabetic Ketoacidosismentioning
confidence: 99%
“…In patients with mitochondrial disease, significant widespread reductions in FA values have been shown in white matter tracts, in some cases in normal-appearing white matter. Mean diffusivity values are increased [49]. It has been reported on a limited basis in acute and long-term followup in which serial diffusion tensor imaging revealed a stroke-like pattern with an initial strong reduction of the ADC followed by elevated values after clinical recovery [50,51].…”
Section: Strokes In Nonvascular Territoriesmentioning
confidence: 99%